DESCRIPTION OF PARASITES IN FAECAL SAMPLES COLLECTED IN PLAZAS OF DOWNTOWN TEMUCO, CHILE - Olivares, Pamela (2014)
The aim of this study was to determine the level of contamination of public plazas in the city of Temuco with parasitic forms through dog faeces. A total of 102 faecal samples were collected in eight plazas of the city centre. Samples were processed by the sedimentation-flotation method (Teuscher method). The 89.2% of the samples resulted positive for a parasitic form, where strongyle-type eggs (69.6%) within the Phylum Nematoda and the oocysts of Isospora within the Phylum Protozoa (6.8%) were the most frequent. Half of the samples were poliparasitic where the triparasitism reached 21.5% of all samples. The findings indicate a polluted environment and poor waste management in the city center.